Pemberdayaan masyarakat dalam kecukupan minum untuk perawatan hipertermia berbasis Kartu Pintar Minum - Juartika, Wella; Feri, Jhon; Artamevia, Gery; Yulistiana, Dini (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
Hyperthermia is a serious health problem that can lead to various complications, including heat exhaustion and heat stroke, if not properly managed. One of the most effective strategies to prevent and manage hyperthermia is ensuring adequate daily fluid intake. This community service program was designed to increase public understanding of the importance of hydration, encourage healthier water-drinking behaviors, and introduce smart drinking cards as a practical tool for monitoring individual fluid consumption. The program employed a participatory and educational approach, actively involving community members in discussions, demonstrations, and monitoring activities. The implementation of the Student Creativity Program for Community Service was carried out smoothly and in accordance with the planned objectives and schedule. The results of the activities indicated that the empowerment program based on smart drinking cards significantly improved community knowledge regarding hydration and positively influenced daily drinking habits. Therefore, this program is recommended to be continued and expanded to other communities, accompanied by regular mentoring and evaluation to ensure long-term sustainability and consistent behavioral change.